2019
DOI: 10.1002/ijfe.1796
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of performance in the Eurozone banking sector: Core versus periphery Eurozone economies

Abstract: In the present study we provide a thorough analysis of the effects that a group of bank‐specific as well as industry‐specific determinants along with the regulatory framework developed under the three pillars of Basel II agreement (capital stringency, official disciplinary power and private monitoring) have on the performance of Eurozone banking sector over the period 2007–2016. To this end, we conduct a systematic comparative analysis of the determinants of the performance of the banking sector in periphery E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
3
1
Order By: Relevance
“…In terms of LLP, we observe a significant negative and a rather strong effect on both profitability measures, in contrast with Agoraki et al (2021) that found a positive effect of LLP on bank performance given by stocks return. In our study, an increase of 1 p.p.…”
Section: Dynamic Model Of Profitabilitycontrasting
confidence: 99%
See 1 more Smart Citation
“…In terms of LLP, we observe a significant negative and a rather strong effect on both profitability measures, in contrast with Agoraki et al (2021) that found a positive effect of LLP on bank performance given by stocks return. In our study, an increase of 1 p.p.…”
Section: Dynamic Model Of Profitabilitycontrasting
confidence: 99%
“…By controlling for the potential profitability differences between peripheral and core countries' banking systems, we fill a relevant gap in the literature that, to the best of our knowledge, was only addressed by Agoraki et al (2021). Their study analyses the effects that a group of bank-specific and industry-specific determinants along with the regulatory framework have on bank performance, measured by stock returns, of periphery Eurozone countries (Greece, Italy, Spain and Portugal) and core Eurozone countries (France and Germany).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, employing high proportions of them could lead to low profitability. Agoraki et al [ 42 ] also suggest that bank profits are negatively related to their leverage.…”
Section: Discussionmentioning
confidence: 99%
“…ROA: Profitability represents a difficult concept in terms of its measurement and definition (Almaqtari et al 2019;Teixeira et al 2020). As shown in the academic literature and professional and industrial reports, there is no single, universallyrecognised financial formula to measure profitability (Burca et al 2014;Agoraki et al 2019). Academics have used a range of different, though related, mathematical expressions to measure profitability (Bikker and Vervliet 2018).…”
Section: Profitabilitymentioning
confidence: 99%